Implementasi Manajemen Konfik Di MI Muhammadiyah Garongan - Noer Hanifah Lestari; Linda Kurniawati; Farid Setiawan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The aim of this research was to find out how conflict management was implemented at MI Muhammadiyah Garongan. The method used is a qualitative method through observation and interviews taking place at MI Muhammadiyah Garongan with two interviewees, namely the Principal and class teacher at MI Muhammadiyah Garongan. The results of the research show that at MI Mammadiyah Garongan, Conflict Management has been implemented, where there are several factors that cause conflict at MI Muhammadiyah Garongan to occur, including: First, there is a transition period from kindergarten to elementary school. Second, literacy constraints. Third, factors from the students' parents. Fourth, the curriculum factor is inadequate school facilities and infrastructure. Given the factors that cause this conflict, MI Muhammadiyah Garongan also has countermeasures through: First, school policies. Second, providing literacy. Third, build good relationships with students' parents.